Educational barriers of nurses caring for sick and at‐risk infants in India. (8th August 2014) - Campbell‐Yeo, M.; Deorari, A.; McMillan, D.D.; Singhal, N.; Vatsa, M.; Aylward, D.; Scotland, J.; Kumar, P.; Joshi, M.; Kalyan, G.; Dol, J.
<x xml:space="preserve">Abstract</x> Aim To gain ideas and information from healthcare providers to optimize the education and clinical practices of nurses caring for sick or at‐risk newborns in India. Background Improving infant survival has been identified as a Millennium Development Goals; however, India still faces many challenges with 3.1 million neonatal deaths and 2.6 million stillbirths annually. Skilled nursing care has been associated with decreased morbidity and mortality in newborns. However, core competencies in newborn care education and training are lacking for nurses. Methods Qualitative data were collected from 12 focus groups with 101 newborn care providers from three areas of India as well as from a 2‐day stakeholders' meeting. Data analysis was undertaken using descriptive and thematic content analysis. Results Perceived challenges included limited manpower and high nurse turnover, lack of access to evidence‐based orientation to newborn care and problems with access to appropriate learner‐based, neonatal training. Relevant, ongoing education opportunities, led by nursing leaders were identified to be important solutions. Conclusion Findings provide insight into the current healthcare system in India with specific reference to the nursing care of at‐risk newborns. There is a lack of existing resources to provide standardized and specific orientation curricula for nurses. Implications for Nursing and Health Policy Policy makers in health and education need to: support and enact learner‐based orientation and continuing educational opportunities as well as ongoing competency‐based education programmes; encourage nurse leader involvement and support; and provide sustainable system‐related supports. Nurses and other health providers need to work together to influence government policy.